A Review on Analysing the Impact of IoT on Smart Agriculture - Singh Sengar, Hiresh; Rai, Sakshi (International Journal of Computer Sciences and Engineering, 2024)
Nowadays technology has made significant strides, with countless of devices and techniques available in the agricultural sector. The Internet of Things (IoT) plays a vital role in increasing production, efficiency, and worldwide market reach, as well as lowering human involvement, expenditure, and time, all of which are crucial in the sector of agriculture. The Internet of Things (IoT) is a system that connects computing devices, objects, mechanical and digital devices, and living beings. These IoT components are given unique identifiers and can send data across a network without requiring human-to-human or human-to-computer interaction. To increase productivity, IoT partners with agriculture to enable smart farming. In this paper, we study the role of IoT in the sector of agriculture to make it smart farming.